The Final Fight: An Analysis of Metaphors in Online Obituaries of Professional Athletes. (September 2019) - Heynderickx, Priscilla C.; Dieltjens, Sylvain M.; Oosterhof, Albert
In literature, obituaries from different cultures and languages have been studied on different levels and from different perspectives. One of the popular research topics is the use of metaphors, since metaphors help to cope with death, which in modern society is still a taboo. This article presents a bottom-up, primarily qualitative analysis of the metaphors in 150 obituaries of sportspeople, published in online versions of newspapers/magazines and on the Internet. As expected, the obituaries contain the traditional metaphors of death. Also more original, creative metaphors are introduced to describe death in a euphemistic way. Some of those have a link to sports but not systematically to the sport practiced by the deceased.